Antioxidant Activity and other Physicochemical Characteristics of Different Propolis Extracts - Alaa Zam ,; Mohammad Othman, (Journal of Pharmacy and Nutrition Sciences, 2018)
This study was to investigate the antioxidant activity of three different extracts of propolis (Ethanolic 50%, methanolic 100% and aqueous extracts) with some of their physicochemical aspects. Ethanolic extract was analyzed by LC-MS, while the methanolic extract was analyzed by GC-MS in order to screen polyphenols and volatile compounds in the sample, the identity of these components were achieved by means of comparing their mass spectra with previous published studies. Forrier transformation infrared spectroscopy (FTIR) was conducted on the methanolic extract and crude propolis samples to gain an overview of some physical characteristics. The antioxidant activities of the three extracts were measured by DPPH scavenging ability and FRAP assay. LC-MS and GC-MS allowed the identification of 19 phenolic and 17 volatile compounds. The most abundant phenolics found in our sample correspond with p-Coumaric benzyl ester, Pinobanksin-3-O-acetate, Caffeic acid benzyl ester and pinocembrin, as they showed the highest peaks in the total ion chromatogram (TIC). In addition, the most abundant volatile compounds showed a high level of agreement with δ-Cadinene and γ- Terpinen.Furthermore, Ethanol 50% extract showed the strongest antioxidant activity, which has a significant correlation with its high polyphenolic content.